Incidence and outcomes of adverse drug reactions to first‐line anti‐tuberculosis drugs and their effects on the quality of life: A multicenter prospective cohort study. Issue 11 (9th August 2022) - Choi, Hayoung; Park, Hang A.; Hyun, In Gyu; Kim, Joo‐Hee; Hwang, Yong‐Il; Jang, Seung Hun; Sim, Yun Su; Shin, Tae Rim; Ko, Yousang; Ban, Ga Young; Hong, Ji Young; Lee, Chang Youl; et al.
Abstract: Background: In tuberculosis (TB) treatment, adverse drug reactions (ADRs) can interrupt treatment and decrease the quality of life (QoL). We aimed to prospectively investigate the incidence of ADRs to first‐line anti‐TB drugs and related outcomes and QoL. Methods: Adult patients with TB who had been treated with first‐line anti‐TB drugs in five Korean hospitals were enrolled. ADR questionnaire surveys and blood tests were performed four times serially, and QoL was assessed on the fourth TB treatment week (±2 weeks). Results: Of 410 enrolled patients with TB (males, 62%; mean age, 52.1 ± 18.1 years [those aged ≥65 years, 26.6%]), 67.8% experienced any ADRs (≥ grade 2) to TB drugs. The most common ADR was fatigue (53.2%), followed by itching (42.7%) and anorexia (41.7%). Older adult patients experienced relatively more ADRs, including anorexia, dyspepsia, rash, dizziness, anemia, abnormal hepatic/renal function tests, and increased uric acid levels ( p < 0.05). Treatment regimens changed for 9.5% of patients owing to ADRs to anti‐TB drugs. Patients with any ADRs and older adult patients had significantly lower QoL than their counterparts ( p < 0.05). Old age (odds ratio [OR], 1.02) and being male (OR 2.65) were independently associated with ADRs, whereas active smoking (OR 4.73) and a relatively long treatment phase (OR 5.13) were independently associated with hepatotoxicity. Conclusion: ADRs to first‐line anti‐TB drugs were common and related to relatively low QoL, especially among older adults. Although 9.5% of patients had ADR‐related regimen changes, most patients with ADRs completed treatments successfully.